Distúrbio do sono em pacientes com esclerose múltipla : a relação entre fadiga e sonolência excessiva diurna - Braga, Douglas Martins [UNIFESP] (2017)
Sleep disorders in patients with multiple sclerosis have various causes and interfere with daytime wakefulness. Objective: This study assessed the correlation between fatigue, excessive daytime sleepiness and level of disability. Method: Retrospective review of medical records from patients with multiple sclerosis to collect data on severity of fatigue, disability, daytime sleepiness, and depression. From 912 medical records reviewed, 122 reported daytime sleepiness: 67% had relapsing remitting, 12% had primary progressive, and 21% had secondary progressive. Results: In 95% of the patients with relapsing remitting who complained of daytime sleepiness and fatigue, association was found between these symptoms and neurological disability. Patients with relapsing remitting who complained of daytime sleepiness and fatigue also experienced depression (p = 0.001). No association between fatigue, excessive daytime sleepiness, depression, and disability was found in patients with progressive disease. Conclusion: In relapsing remitting, there is correlation between functional disability, excessive daytime sleepiness and fatigue, a finding not confirmed in primary progressive and secondary progressive form.